اسلام اورسرمایہ دارانہ نظام ہائےِمعیشت کے اہم پہلوؤں کا تقابلی مطالعہ (Al-Qamar, 2020)
Capitalism enjoys popularity on global level in present era. However, if this western economic system is evaluated deeply and its results are assessed, it seems that it is just a claim, because this economic system causes deprivation of basic rights of an individual despite of fulfillment his basic necessities ideally. On the contrary, the Islamic economic system has high virtues such as self-sacrifice and compassion. In this article, an effort has been made of analysis of moral values of western economic system and subsequently a comparison of the same with Islamic economic system. It finds that key aspects of the capitalist economy are self-interest, monopoly, selfishness, materialism and narcissism. Islamic economics, on the other hand, focuses on human compassion, self-sacrifice and the collective interest rather than the individual. On this basis, the welfare of humanity lies in the Islamic principles of economy.
Keywords: Capitalism; Islamic Economic; values; comparison